Zvýsená reaktivita lymfocytů u nemocných s chronickým selháním ledvin - Korcáková, L; Svobodová, J (Casopis lekaru ceskych, 1993)
Lymphocytes isolated from peripheral blood of patients with irreversible renal failure and cultivated in non-stimulated cell cultures incorporated significantly more 3H-thymidine and released more beta-2-microglobulin than lymphocytes of the patients' healthy relatives (possible kidney donors) and than lymphocytes of non-related blood donors.
Keywords: Lymphocyte Activation; lymfocyty; aktivace lymfocytů; lidé; Lymphocytes; chronické selhání ledvin; test smíšené lymfocytární kultury; Humans; Lymphocyte Culture Test, Mixed; Kidney Failure, Chronic